Analisis Potensi Penerimaan Retribusi Parkir Terhadap Pendapatan Asli Daerah Kabupaten Jayapura - Urip, Transna Putra; Karubaba, Blandina (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
The purpose of this study is to find out how big the potential and effectiveness of parking fees is in Jayapura Regency. by using the analysis method of potential parking fees and the ratio of effectiveness. Based on the results of the discussion, it can be concluded (a) From the calculation results above, PAD is obtained from the management of parking fees. for 2-wheeled vehicles with a parking rate of IDR 1,000 with a parking vehicle of 959,040 vehicles/year, thus the potential daily revenue is IDR 959,040,000, a 4-wheeled vehicle tariff is IDR 2,000 with a total of 524,160 vehicles/year, so total potential revenue of Rp. 1,048,320,000. (b) 2016 with an effectiveness rate of 77% which is in the criteria that are quite effective because it is less than 100%. In 2017 and 2018 the effectiveness rate was 112%, 131% with very effective criteria, in 2019 the effectiveness rate was 92% with effective criteria, in 2020 and 2021 the effectiveness rate was 115%, 102, with very effective criteria. (c). The contribution of parking tax to local taxes is still very low, with an average of 3.35%. Keywords: Potential for Parking Retribution, Local Own Revenue